2014
DOI: 10.1093/nar/gku1092
|View full text |Cite
|
Sign up to set email alerts
|

Cyclebase 3.0: a multi-organism database on cell-cycle regulation and phenotypes

Abstract: The eukaryotic cell division cycle is a highly regulated process that consists of a complex series of events and involves thousands of proteins. Researchers have studied the regulation of the cell cycle in several organisms, employing a wide range of high-throughput technologies, such as microarray-based mRNA expression profiling and quantitative proteomics. Due to its complexity, the cell cycle can also fail or otherwise change in many different ways if important genes are knocked out, which has been studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
221
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(233 citation statements)
references
References 30 publications
10
221
2
Order By: Relevance
“…Of the 51 Rtf1-specific genes categorized into GO: 0022402 cell cycle process, 44 were downregulated by Rtf1 knockdown while 7 were upregulated by Rtf1 knockdown. A search of Cyclebase 3.0, a cell cycle-dependent gene expression database (52), indicated that 21 of the 44 downregulated genes are highly expressed in S, G 2 , and/or M phase. These findings are consistent with the idea that the 21 genes, including BUB1, CCNA2, CCNB2, CENPA, and PLK1, were downregulated through an indirect effect of an altered cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 51 Rtf1-specific genes categorized into GO: 0022402 cell cycle process, 44 were downregulated by Rtf1 knockdown while 7 were upregulated by Rtf1 knockdown. A search of Cyclebase 3.0, a cell cycle-dependent gene expression database (52), indicated that 21 of the 44 downregulated genes are highly expressed in S, G 2 , and/or M phase. These findings are consistent with the idea that the 21 genes, including BUB1, CCNA2, CCNB2, CENPA, and PLK1, were downregulated through an indirect effect of an altered cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Cdk1 substrate expression could be cell cycle regulated, in which case Cdk1 phosphorylation would provide an additional layer of regulation to fine-tune substrate function. It was previously shown by Whitfield et al (73) that of 13,912 genes profiled, 588 are cell cycle regulated (74). We mapped proteins on which we identified phosphorylation sites that responded to either Flavopiridol or RO-3306 to gene sequences present in that microarray analysis (73).…”
Section: Quantitative Analysis Of the Phosphoproteome Of Flavopiridolmentioning
confidence: 94%
“…In particular, genome-wide transcriptome data provides information on the expression levels of informative cell-cycle marker genes, which have been carefully annotated in several systems and cell types (e.g., in human, yeast and Arabidopsis [16]). Consequently, we reasoned that these genes can be used to infer the cell cycle phase directly from the transcriptome.…”
Section: Introductionmentioning
confidence: 99%